Prenatal diagnosis and postnatal follow-up of 15 fetuses with 16p13.11 microduplication syndrome - Zhao, Yan; Song, Lina; Zhang, Shuxia; Hou, Fei; Shan, Shan; Jin, Hua (Frontiers in Genetics, 2024)
The clinical phenotypes of 16p13.11 microduplication syndrome have been extensively reported in previous studies, mostly about adults and children, with limited information available on fetal cases. This study aims to explore the genotype-phenotype correlation of fetuses with 16p13.11 microduplication syndrome and analyze the characteristics of prenatal diagnosis indications and provide clinical information for prenatal and postnatal genetic counseling.We conducted a retrospective analysis of 3,451 pregnant women who underwent invasive prenatal diagnosis for SNP array between January 2018 and December 2022 at the Jinan Maternal and Child Health Hospital. Descriptive statistical analysis was performed on the prenatal diagnosis indications, pedigree analysis, pregnancy outcomes and postnatal follow-up of 15 fetuses with 16p13.11 microduplication syndrome. Results: SNP array revealed that 15 fetuses had duplications in the 16p13.11 region with varying prenatal diagnosis indications. Among the cases, 6/15 exhibited ultrasound abnormalities, 5/15 had abnormal chromosomal copy number variations as indicated by non-invasive prenatal testing (NIPT), one case involved advanced maternal age, and 3/15 had other abnormalities. 16p13.11 microduplication syndrome was closely related to ultrasound abnormalities, especially structural abnormalities and soft marker anomalies (abnormal ultrasonic soft indicators), while the indication of NIPT could improve the detection rate of copy number variations (CNVs) in this region. Only 7/15 fetuses underwent pedigree verification, with one case of de novo 16p13.11 microduplication, and the others inherited from one parent. Pregnancy was terminated in 2/15 cases and the outcome of one case is unknown due to loss to follow-up. Among the remaining cases, only one case exhibited a ventricular septal defect, while another presented with omphalocele. No other obvious abnormalities were reported postnatally.The prenatal phenotypes of fetuses with 16p13.11 microduplication were highly associated with ultrasound abnormalities but lacked specificity.Comprehensive genetic tracing, outcome analysis, and follow-up are essential for providing accurate prenatal and postnatal genetic counseling.